2007
DOI: 10.1016/j.jcrs.2007.06.067
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of the Acri.LISA bifocal intraocular lens

Abstract: The Acri.LISA 366D IOL provided a satisfactory full range of vision; a high level of uncorrected and corrected distance, intermediate, and near acuity; and improved contrast sensitivity under photopic and mesopic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
63
1
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 21 publications
15
63
1
6
Order By: Relevance
“…All studies 20 30,36,38,40 show that the new AcrySof ReSTOR aspheric IOL with a +3.00 D addition provides better intermediate visual performance than AcrySof ReSTOR aspheric IOL with +4.00 D addition, with no decrease for either distance or near visual acuities. It seems that the lower addition of the IOL plays an important role in the improvement of visual acuity for intermediate distances.…”
Section: Hybrid Multifocal Iols Madrid-costa Cerviño Ferrer-blascomentioning
confidence: 95%
See 3 more Smart Citations
“…All studies 20 30,36,38,40 show that the new AcrySof ReSTOR aspheric IOL with a +3.00 D addition provides better intermediate visual performance than AcrySof ReSTOR aspheric IOL with +4.00 D addition, with no decrease for either distance or near visual acuities. It seems that the lower addition of the IOL plays an important role in the improvement of visual acuity for intermediate distances.…”
Section: Hybrid Multifocal Iols Madrid-costa Cerviño Ferrer-blascomentioning
confidence: 95%
“…13 Montés-Micó and coauthors 13 reported that patients with multifocal IOLs had worse CSF under dim conditions. Studies evaluating the CSF after hybrid multifocal IOL implants 20,26,29,30,32,35,38,39,43,[46][47][48][49][50] also found a reduction in contrast sensitivity when the luminance level was reduced, particularly for higher spatial frequencies. This trend agrees with classic data on the effect of the luminance level on contrast sensitivity.…”
Section: Contrast Sensitivitymentioning
confidence: 97%
See 2 more Smart Citations
“…Bifocal refractive (1)(2)(3) , diffractive (4)(5)(6)(7) , spherical hybrid (8)(9)(10)(11) and aspheric hybrid (12)(13)(14)(15)(16) IOLs generate two focal points along the optical axis to provide good monocular uncorrected distance and near visual acuity (UCVA and UNVA, respectively) as well as functional intermediate vision. The bifocal IOLs have also been implanted in RLE with good results at distance and near vision (17)(18)(19)(20)(21)(22)(23)(24)(25) .…”
Section: Introductionmentioning
confidence: 99%